The Quest for Anti-inflammatory and Anti-infective Biomaterials in Clinical Translation - Griffith, May; Islam, Mohammad M.; Edin, Joel; Papapavlou, Georgia; Buznyk, Oleksiy; Patra, Hirak K. (Frontiers in Bioengineering and Biotechnology, 2016)
Biomaterials are now being used or evaluated clinically as implants to supplement the severe shortage of available human donor organs. To date however, such implants have mainly been developed as scaffolds to promote the regeneration of failing organs due to old age or congenital malformations. In the real world, however, infection or immunological issues often compromise patients. For example, bacterial and viral infections can result in uncontrolled immunopathological damage and lead to organ failure. Hence, there is a need for biomaterials and implants that not only promote regeneration but also address issues that are specific to compromised patients such as infection and inflammation. Different strategies are needed to address the regeneration of organs that have been damaged by infection or inflammation for successful clinical translation. Therefore, the real quest is for multi-functional biomaterials with combined properties that can combat infections, modulate inflammation and promote regeneration at the same time. These strategies will necessitate the inclusion of methodologies for management of the cellular and signaling components elicited within the local microenvironment. In the development of such biomaterials, strategies range from the inclusion of materials that have intrinsic anti-inflammatory properties, such as the synthetic lipid polymer, 2-methacryloyloxyethyl phosphorylcholine (MPC), to silver nanoparticles that have anti-bacterial properties, to inclusion of nano- and micro-particles in biomaterials composites that deliver active drugs. In this present review, we present examples of both kinds of materials in each group along with their pros and cons. Thus, as a promising next generation strategy to aid or replace tissue/organ transplantation, an integrated smart programmable platform is needed for regenerative medicine applications to create and/or restore normal function at the cell and tissue levels. Therefore, now it is an utmost important to develop integrative biomaterials based on multi-functional biopolymers and nanosystem for their practical and successful clinical translation.